Pembuatan Pakan Berbahan Limbah Usus Ayam Untuk Budidaya Ikan Lele dI Kelurahan Pai, Kota Makassar - Chadijah, Andi; Salam, Nur Insana; Puspitasari, Dewi; Rahmi, Rahmi (Suluah Bendang: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2021)
The catfish farming group in Pai Village faces problems related to the high price of commercial feed, so they use chicken intestine waste feed. This activity's purpose is the manufacture of catfish feed made from chicken intestine flour in Pai Village, Makassar City. The method used is through socialization, discussion and question and answer, and training in making feed using chicken intestine flour as raw material. The community service activities carried out went smoothly and received enthusiasm from the cultivator group community. Cultivators can make feed by utilizing chicken intestine waste and apply it in catfish farming activities.